Lateral diffusion of proteins in cell membrane: the anomalous case - Lubelski, Ariel; Klafter, Joseph (Diffusion Fundamentals, 2005)
We present a method describing the lateral movement of proteins in cell membranes as observed in FRAP experiments. We extend earlier results derived for normal diffusion [1] to account for the case of anomalous subdiffusion. Our analytic closed forms are compared to computer simulations of anomalous diffusion and both show excellent agreement. The approach sheds light on the behavior of proteins in such complex systems and provides a tool to analyze experimental results.